SARM1 knockout does not rescue neuromuscular phenotypes in a Charcot‐Marie‐Tooth disease Type 1A mouse model. Issue 1 (13th February 2022) - Moss, Kathryn R.; Johnson, Anna E.; Bopp, Taylor S.; Yu, Andrew T.; Perry, Ken; Chung, Tae; Höke, Ahmet
Abstract: Charcot‐Marie‐Tooth disease Type 1A (CMT1A) is caused by duplication of the PMP22 gene and is the most common inherited peripheral neuropathy. Although CMT1A is a dysmyelinating peripheral neuropathy, secondary axon degeneration has been suggested to drive functional deficits in patients. Given that SARM1 knockout is a potent inhibitor of the programmed axon degeneration pathway, we asked whether SARM1 knockout rescues neuromuscular phenotypes in CMT1A model (C3‐PMP) mice. CMT1A mice were bred with SARM1 knockout mice to generate CMT1A/SARM1 −/− mice. A series of behavioral assays were employed to evaluate motor and sensorimotor function. Electrophysiological and histological studies of the tibial branch of the sciatic nerve were performed. Additionally, gastrocnemius and soleus muscle morphology were evaluated histologically. Although clear behavioral and electrophysiological deficits were observed in CMT1A model mice, genetic deletion of SARM1 conferred no significant improvement. Nerve morphometry revealed predominantly myelin deficits in CMT1A model mice and SARM1 knockout yielded no improvement in all nerve morphometry measures. Similarly, muscle morphometry deficits in CMT1A model mice were not improved by SARM1 knockout. Our findings demonstrate that programmed axon degeneration pathway inhibition does not provide therapeutic benefit in C3‐PMP CMT1A model mice. Our results indicate that the clinical phenotypes observed in CMT1A mice are likely caused primarily by prolonged dysmyelination, motivate further investigation into mechanisms of dysmyelination in these mice and necessitate the development of improved CMT1A rodent models that recapitulate the secondary axon degeneration observed in patients.